Correlation of sLOX-1 and CSF1 with the pathological progression of hypoxic-ischemic encephalopathy in neonatal rats: Relationship between sLOX-1, CSF1 and hypoxic-ischemic brain - Huang, Jun; Jiang, Wentao; Pan, Junping; Xu, Xuetao (Cellular and Molecular Biology, 2023)
To provide clinical evidence for the management of hypoxic-ischemic encephalopathy (HIE) by analyzing the role of soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1) and colony-stimulating factor-1 (CSF1) in the disease. We purchased 15 Sprague-Dawley (SD) rat pups and randomized them into five groups (n=3), of which one group was untreated as the control group and the other four were modeled by HIE. After modeling, a group was treated as a model group without any treatment, another group was injected with sLOX-1-silencing lentiviral vector (sLOX-1-si group), and the third and fourth were injected with CSF1-silencing lentiviral vector (CSF1-si group) and an equal amount of normal saline (blank group), respectively. After the corresponding intervention, the rat tissue in each group was obtained to observe the pathological injury by HE and TUNEL staining. In addition, sLOX-1, CSF1, 5-hydroxytryptamine (5-HT), dopamine (DA), and norepinephrine (NE) levels in brain tissue of each group were determined. The model group showed more severe pathological damage of the hippocampus and higher neuronal apoptosis than the control group. Besides, higher sLOX-1 and CSF1 levels and lower 5-HT, DA and NE contents were identified in the model group versus the control group (P<0.05). Compared with the blank group, sLOX-1-si and CSF1-si groups showed significantly alleviated hippocampal damage, inhibited neuronal apoptosis, reduced 5-HT, DA, NE, Bax, and cl-caspase-3, and increased Bcl-2 (P<0.05). Silencing sLOX-1 and CSF1 expression ameliorated the pathological injury of HIE and inhibited neuronal apoptosis.